IMPLEMENTASI PERDA NO 6 TAHUN 2002 TENTANG IZIN USAHAPERTAMBANGAN DAERAH DI DESA SETAMBANG - Setipa E.21108045, Katerina (FISIP Universitas Tanjungpura, 2013)
The Writing article is intended to generate recommendations on the implementation ofRegulation No. 6 of 2002 on Mining Permit area. This study focused on the implementation of RegulationNo. 6 of 2002 on Mining Permit Area, which includes communication, resources both human andfinancial resources, disposition implementer, ie the nature and characteristics, and structure of thebureaucracy. The purpose of this study was to determine the communication, resources, and thedisposition of implementers to know the structure of the bureaucracy in the implementation processBylaw No. 6 of 2002 on Mining Permit area in the Desa Setambang Kecamatan Sepauk KabupatenSintang. The focus of the research is trying to discuss using qualitative methods. Based on this research isfound that the communication has not been established and running well, human resources has met thequalifications but without the support of financial resources, the disposition of implementers not fullymeet the requirements, and bureaucratic structure is not in accordance with the Standard OperatingProcedureÂ Â Keywords: Implementation of Regional Regulation, Business License, Standard Operating ProceduresÂ